Mucoadhesive Hydrogel Patch Loaded With Dox To Treat Chronic Wounds - Saima Hafsah; Dr. Bargavi (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Chronic wounds represent a significant clinical burden due to their persistent inflammatory state, susceptibility to infection, and impaired healing response. This study aimed to develop and characterize a mucoadhesive hydrogel patch loaded with doxycycline (DOX) as a localized therapeutic strategy for chronic wound management. The patch was formulated using a composite of 3% cellulose and 5% chitosan, incorporating 100 mg of doxycycline into the hydrogel matrix. The developed system was subjected to comprehensive characterization including scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), contact angle measurement, hemocompatibility, and in vitro cytotoxicity assays. Results demonstrated that the patch exhibited a porous and interconnected morphology, favorable hydrophilic surface properties, excellent blood compatibility, and high cell viability. The incorporation of doxycycline was confirmed without significant chemical alteration of the polymer network. The findings suggest that this mucoadhesive hydrogel patch can provide sustained drug release, adhere effectively to moist wound surfaces, and create a conducive healing microenvironment. In conclusion, the doxycycline-loaded cellulose-chitosan hydrogel patch shows promising potential as an advanced wound dressing for the treatment of chronic wounds, combining controlled drug delivery with biocompatible and mucoadhesive properties.